Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.eururo.2017.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Three-year Safety of Radium-223 Dichloride in Patients with Castration-resistant Prostate Cancer and Symptomatic Bone Metastases from Phase 3 Randomized Alpharadin in Symptomatic Prostate Cancer Trial

Abstract: Updated Alpharadin in Symptomatic Prostate Cancer (ALSYMPCA) trial findings show that radium-223 remained well tolerated during treatment and up to 3 yr after each patient's first injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 18 publications
3
54
2
Order By: Relevance
“…Although we cannot rule out the contribution of radium-223 therapy to the increase in anaemia seen in our sample, we can say that pts with lower haemoglobin levels at the start of therapy because of a higher number of metastases, had a similar trend in haemoglobin levels during radium-223 treatment with an adequate supportive care for anaemia than pts with fewer metastases. This is in line with literature 16,17 and the results from the ALSYMPCA trial in which anaemia as a serious adverse event was reported in 8% of pts with radium-223 and in 9% of pts treated with placebo 10 . It is also in agreement with real-world experience 18 , and in a study in 92 pts with mCRPC only baseline haemoglobin and ECOG PS were www.nature.com/scientificreports www.nature.com/scientificreports/ significantly correlated with OS among all clinical parameters 19 .…”
Section: Discussionsupporting
confidence: 91%
“…Although we cannot rule out the contribution of radium-223 therapy to the increase in anaemia seen in our sample, we can say that pts with lower haemoglobin levels at the start of therapy because of a higher number of metastases, had a similar trend in haemoglobin levels during radium-223 treatment with an adequate supportive care for anaemia than pts with fewer metastases. This is in line with literature 16,17 and the results from the ALSYMPCA trial in which anaemia as a serious adverse event was reported in 8% of pts with radium-223 and in 9% of pts treated with placebo 10 . It is also in agreement with real-world experience 18 , and in a study in 92 pts with mCRPC only baseline haemoglobin and ECOG PS were www.nature.com/scientificreports www.nature.com/scientificreports/ significantly correlated with OS among all clinical parameters 19 .…”
Section: Discussionsupporting
confidence: 91%
“…In ALSYMPCA, radium-223 was also associated with a significantly prolonged time to symptomatic skeletal events (SSEs) and reduced alkaline phosphatase (ALP) levels vs placebo ( p < 0.001 for both), and was well tolerated [ 11 ]. In addition, no second primary treatment-related malignancies were reported when patients were followed for up to 3 years [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to all hematologic adverse events, thrombocytopenia was more prevalent in the Xofigo group (12%) compared to the placebo group (6%), and neutropenia was also more prevalent in the Xofigo group (5%) compared to placebo (1%). Anemia had the same prevalence in the Xofigo group and placebo (31% and 31%, respectively) [10].…”
Section: Discussionmentioning
confidence: 81%